Big deal : mergers and acquisitions in the digital age - Wasserstein, Bruce (New York, NY : Warner Business Books, 2000)
This title looks at the world of mergers and acquisitions. Bruce Wasserstein has worked on over 1000 deals and reveals the inside story of the billion-dollar deals that shape America's economy.
Originally published: New York : Warner Books, 2000. With a new pref.
Includes bibliographical references (p. 896-901) and index.
oif 30/01/15
Loan
Keywords: Consolidation and merger of corporations -- United States; Conglomerate corporations -- United States; Corporate reorganizations -- United States; Corporations -- United States